Novel hyperthermia applicator system allows adaptive treatment planning: Preliminary clinical results in tumour‐bearing animals. (11th September 2017) - Dressel, S.; Gosselin, M.‐C.; Capstick, M. H.; Carrasco, E.; Weyland, M. S.; Scheidegger, S.; Neufeld, E.; Kuster, N.; Bodis, S.; Rohrer Bley, C.
Abstract : Hyperthermia (HT) as an adjuvant to radiation therapy (RT) is a multimodality treatment method to enhance therapeutic efficacy in different tumours. High demands are placed on the hardware and treatment planning software to guarantee adequately planned and applied HT treatments. The aim of this prospective study was to determine the effectiveness and safety of the novel HT system in tumour‐bearing dogs and cats in terms of local response and toxicity as well as to compare planned with actual achieved data during heating. A novel applicator with a flexible number of elements and integrated closed‐loop temperature feedback control system, and a tool for patient‐specific treatment planning were used in a combined thermoradiotherapy protocol. Good agreement between predictions from planning and clinical outcome was found in 7 of 8 cases. Effective HT treatments were planned and verified with the novel system and provided improved quality of life in all but 1 patient. This individualized treatment planning and controlled heat exposure allows adaptive, flexible and safe HT treatments in palliatively treated animal patients.